Motion control strategy of an underwater glider in the presence of external disturbances - Ullah, B. (Asian Research Publishing Network, 2016)
This paper describes motion control strategy of an underwater glider in the presence of external disturbances based on state feedback and full order observer feedback. In this paper, we will be concerned only with the phugoid motion in the vertical plane. A control strategy for the glider was implemented with fast and stable convergence. Simulation results show that the open loop system is controllable and observable. The results suggest the use of a well-known guidance for fast tracking and stability control. Â© 2006-2016 Asian Research Publishing Network (ARPN).